The Effect of Tummy Time Exercise on Gross Motor Skills in Babies Aged 3-6 Months - Hanik Khairun Nisa; Suci Sulistyorini (Journal of Educational Innovation and Public Health, 2024)
Babies who experience delays in gross motor development will reduce the baby's creativity in adapting and make it difficult for the baby to recognize the surrounding environment. Growth and development is a continuous process that occurs since conception and continues until adulthood. One of the early steps to accompany child growth and development is carried out through stimulation, namely stimulation to improve infant motor skills with tummy time exercise. The purpose of this study was to determine the effect of Tummy time exercise on gross motor skills in infants aged 3-6 months. This study used the methoda quasi-experimental with control group design.Data analysis using the Mann Whitney test.Gross motor development is assessed usingDenver Developmental Screening Test (DDST). The results of this study showThe average gross motor development in the intervention group after tummy time exercise for 3 weeks showed faster gross motor development compared to babies in the control group who were not given intervention. While the p value obtained was 0.000. The conclusion of this study is that tummy time exercise has a strong influence on infant motor development. So it can be recommended to give tummy time exercise to babies.